2015
DOI: 10.1589/jpts.27.155
|View full text |Cite
|
Sign up to set email alerts
|

A study on the relationships between age, work experience, cognition, and work ability in older employees working in heavy industry

Abstract: [Purpose] The purpose of this study was to examine the correlation of age, work experience, cognition, and work ability in older employees working in heavy industry. [Subjects and Methods] The study was conducted using 100 subjects who were over 55 years old and worked in heavy industry. To obtain data, we first had the subjects complete the MoCA-K test and Work Ability Index (WAI). The data were then analyzed by frequency and correlation using statistical software (SPSS 21.0). [Results] Through this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 6 publications
1
30
0
6
Order By: Relevance
“…Other factors such as years of work and the workload (hours of work per week) were not inquired in this study. Nevertheless, previous study found years of working were significantly correlated with age 31) . There were missing values in some of the variables which may affect the precision of the results.…”
Section: Limitations and Strengthsmentioning
confidence: 68%
“…Other factors such as years of work and the workload (hours of work per week) were not inquired in this study. Nevertheless, previous study found years of working were significantly correlated with age 31) . There were missing values in some of the variables which may affect the precision of the results.…”
Section: Limitations and Strengthsmentioning
confidence: 68%
“…The finding on the positive effect between the age of respondents and job performance is not in line with Saks and Waldman (1998) or Fauzilah (2012). But, it is in support of Ng and Feldman (2013) and Chung, et al (2015).…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, the review paper by Ng and Feldman (2013), shows that older employees are less likely to be highly agitated by contract breaches or to retaliate to with unproductive behaviour. Chung et al (2015), document that workability among older workers increases with the enhancement of cognitive ability. Robbins and Judge (2008), reveal that if research separates professionals and nonprofession-als, it will be found that performance levels tend to increase in professionals with increasing age, whereas in nonprofessional performance decreases with age.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As age of workers increases, their ability decreases. Same through in the differences of the physical abilities of the workers who are older, their physical abilities decrease compared to the younger ones which can perform essential responsibilities [9]. Table 2 shows that 73.6% of the respondents are single while only 26.4% of the total number of respondents are Married.…”
Section: Cultural Competence In Caring For Muslim Patientsmentioning
confidence: 98%